CRE-Mediated Transcription and COX-2 Expression in the Pilocarpine Model of Status Epilepticus - Lee, Boyoung (2006)
Status epilepticus (SE) triggers neuronal death, reactive gliosis and remodeling of synaptic circuitry, thus leading to profound pathological alterations in CNS physiology. These processes are, in part, regulated by the rapid upregulation of both cytotoxic and cytoprotective genes. One pathway that may couple SE to transcriptionally-dependent alterations in CNS physiology is the CREB (cAMP response element-binding protein)/CRE (cAMP response element) cascade. Here, we utilized the pilocarpine model of SE on a mouse strain transgenic for a CRE-reporter construct (β-galactosidase) to begin to characterize how seizure activity regulates the activation state of the CREB/CRE pathway in both glia and neurons of the hippocampus. SE triggered a rapid (4–8 hrs post SE) but transient increase in CRE-mediated gene expression in the neuronal sublayers. In contrast to neurons, SE induced a lasting increase (up to 20 days) in CRE-mediated transcription in both reactive astrocytes and microglia. CRE-mediated gene expression correlated with expression of the pro-inflammatory enzyme cyclooxygenase-2 (COX-2). To examine the role of CREB in SE-induced COX-2 expression, we generated a transgenic mouse strain that expresses A-CREB, a potent repressor of CREB-dependent transcription. In these animals, the capacity of SE to stimulate COX-2 expression was markedly attenuated, indicating that CREB is a key intermediate in SE-induced COX-2 expression. Collectively these data show that SE triggers two waves of CREB-mediated gene expression, a transient wave in neurons and a long-lasting wave in reactive glial cells, and that CREB couples SE to COX-2 expression.